2019
DOI: 10.1200/jco.18.02141
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of Immune-Related Cutaneous Adverse Events

Abstract: PURPOSE The aim of the current study was to report the efficacy of topical and systemic treatments for immune-related cutaneous adverse events (ircAEs) attributed to checkpoint inhibitors in an uncontrolled cohort of patients referred to oncodermatology clinics. METHODS A retrospective analysis of patients with ircAEs evaluated by dermatologists from January 1, 2014, to December 31, 2017, at three tertiary care hospitals and cancer centers were identified through electronic medical records. Clinicopathologic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
195
2
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(218 citation statements)
references
References 81 publications
7
195
2
4
Order By: Relevance
“…In this study, we evaluated discordance between recommended and delivered cirAE therapies. We found that cirAEs were common in children, mirroring rates previously reported in adults 5 . cirAE subtypes for which treatment guidelines were available were often untreated or undertreated despite their prevalence.…”
Section: Characteristic Frequency (N = 24) (%)Asupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, we evaluated discordance between recommended and delivered cirAE therapies. We found that cirAEs were common in children, mirroring rates previously reported in adults 5 . cirAE subtypes for which treatment guidelines were available were often untreated or undertreated despite their prevalence.…”
Section: Characteristic Frequency (N = 24) (%)Asupporting
confidence: 78%
“…We retrospectively reviewed the records of patients aged 0‐21 years who received ICIs at Massachusetts General and Boston Children's Hospitals between 2010 and 2019, identifying individuals who developed cirAEs. cirAEs were defined as eruptions emerging after ICI initiation, consistent with established morphologic categories and attributed to the ICI by the treating clinician 5,6 . Additional inclusion criteria were involvement of >1% body surface area and duration >1 day.…”
Section: Characteristic Frequency (N = 24) (%)Amentioning
confidence: 99%
“…Increased AEC, serum IL-6, Il-10 and IgE levels were associated with corticosteroid-refractory adverse events and with grade 3 or greater cutaneous AEs, but the direct accountability of eosinophils was not assessed in these exceptional cases. 24 Even if some severe cutaneous AEs like drug reaction with eosinophilia and systemic symptoms (DRESS) require high-dose corticosteroids, 25,26 multiple recent reports of Eo-irAEs like eosinophilic fasciitis [27][28][29][30] or eosinophilic granulomatosis with polyangiitis 31 suggest that topical or low-dose oral corticosteroids, with or without CSsparing treatments, can give excellent results. Taking account these data, and given that in our work (i) Eo-ir and Eo-irAEs accounted for half of all ICI discontinuations and (ii) no deaths were directly attributable to eosinophil-organ damage, we suggest that the initiation of corticosteroids and the maintenance of the ICI might be an effective therapeutic strategy in patients with moderate-to-severe eosinophilia and whose cancer is under control.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the expansive development and use of targeted tumour therapies, numerous reports have emerged about therapy-associated chronic pruritus (48)(49)(50)(51)(52). The neurokinin-1-antagonist aprepitant seems to have antipruritic potential in such cases (53).…”
Section: Drug-induced Itchmentioning
confidence: 99%